Quantifying the external training loads of highly trained male youth basketball players by year, term and position - Fullagar, H.; Lever, J.; Duffield, R.; Murray, A.; Bartlett, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Current insights on the training demands within highly trained youth basketball academies are limited. Specifically, there remains a lack of detail on the specific physical demands and how they may differ between training blocks or playing positions. Therefore, this study aimed to describe the external training load of highly-trained male youth basketball players, based on training year, term, and playing position. METHODS: Data was collected from 41 male youth basketballers (age = 17.4±0.9 years, height = 203.2±8.3 cm, mass = 91.2±13.3 kg) over two academy seasons from all on-court coach-led training sessions using a commercially available Local Positioning System. The academy provides a fulltime residential basketball development program alongside academic commitments. Linear mixed-models and pairwise comparisons were used to analyse by training year (Y1, Y2, Y3), term (T1, T2, T3, T4) and playing position (Backcourt, Frontcourt) for a variety of external load metrics, with significance set at p*0.05. RESULTS: Results showed no differences in external load metrics between training years. Significant differences existed between training terms, with total distance greater in both T3 and T4 than T1 and 2 (pp<0.03). Total PlayerLoad was significantly greater in T4 than T1 (p<0.001) and 3 (p=0.004). Distance/min was greater in T2, T3 and T4 than T1 (p<0.01). PlayerLoad/min was higher in T4 than T1 and T2 (p<0.01). Backcourt players showed significantly greater distance/min (p=0.011), PlayerLoad/min (p=0.011) and deceleration counts (p<0.001). Overall, limited year-on-year change existed in external training load metrics (p>0.05), though volume (p<0.001) and intensity (p<0.001) differed between terms. Backcourt players completed higher-intensities (p=0.011) than Frontcourt players. CONCLUSION: The results of this study show limited changes in training volume and intensity between years. However, within-season analysis by training term showed significant differences for most training load metrics, indicating a seasonal periodisation of training. Overall, this suggests that this academy environment implements a structured training program within the year, likely related to maximising skill development training. Collectively, this study provides contemporary reference points for practitioners for the external training loads experienced within youth basketball development pathways.